Pengaruh Penerapan Model Pembelajaran Pelatihan Kesadaran Dalam Mata Pelajaran PAI Terhadap Kesadaran Diri Siswa Di SMK Ciledug Al-Musaddadiyah Garut - Salamudin, Ceceng; Ameliasari, Maya (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Self-awareness is crucial in the learning process; however, it often presents challenges. This issue is evident as students frequently lack the ability to recognize their own feelings and behaviors, identify their strengths and weaknesses, demonstrate independence, make appropriate decisions, and effectively express their thoughts, feelings, opinions, and beliefs. Consequently, these students often lack the motivation to engage in more effective learning processes. The Awareness Training Learning Model is proposed as an effective solution to these problems. The purpose of this study is to describe the impact of applying the Awareness Training Learning Model in Islamic Religious Education (PAI) on students' self-awareness at SMK Ciledug Al-Musaddadiyah Garut. This research employs a quantitative descriptive approach. Data collection methods included observation, documentation review, and questionnaires distributed to 27 students who served as the study sample. Data analysis was performed using statistical analysis techniques. The results show that the students' self-awareness had an average score of 4.07, placing it within the interval range of 4.01-5.00, which falls under the "Very Good" category. This indicates a significant improvement in self-awareness after the teachers implemented this model in the learning activities. Similarly, the application of the Awareness Training Learning Model in the PAI subject had an average score of 4.11, also in the "Very Good" category. This demonstrates that this model effectively enhances students' self-awareness in learning. Statistical tests indicate that the application of the Awareness Training Learning Model in PAI has a significant influence, accounting for 79.22% of the improvement in students' self-awareness, while other variables not investigated account for the remaining 20.78%. Keywords: Awareness Training Learning Model, Student Self-Awareness, Islamic Religious Education